THE EFFECT OF PSEUDOMONAS AERUGINOSA SIGNAL QUINOLONE ON THE RHAMNOLIPIDS BIOSYNTHESIS AND RHAMNOSYLTRANSFERASE 2ACTIVITY - Galkin, N.B.; Abedalabas, Mukhlis; Pachomova, E.Yu.; Filipova, T.O. (European Scientific Journal, ESJ, 2014)
Aim: Discovery of the P. aeruginosa ONU 302rhamnolipids biosynthesis andrhamnosyltransferase 2 activity in presence of the Pseudomonas aeruginosaexogenous quorum sensing signal molecule2-heptyl-3-hydroxy-4-quinolon (PQS). Methods. Pseudomonas aeruginosa ONU 302were cultured in the Giss medium with 2% glucose at 37оС 24 h. All discoveries were performed in "plancton-biofilm" system with using of the «Nunclon» 48-well plates. Di- and monorhamnolipids separation conducted by TLC methods and its content was determined by orcinol test. Rhamnosyltransferase 2 (RhlC) activity was analysed in P.aeruginosa cell extracts using arhamnosyltransferase assayspecific for the addition of L-rhamnose to monorhamnolipid. Results. The synthesis of rhamnolipids in control culture is activated from the early stationary phase and the content of the biosurfactants is increasedfivefold up 10 to 24 hour – up 0.66 to 3.44 mg/ml. Addition of increasing concentrations of PQS did not affect the growth ofP.aeruginosa but were enhanced rhamnolipids content and dirhamnolipids proportion in the biosurfactants mixture. After 24 hours total biosurfactant level in culture medium in the presence of 80 μМ PQS was 3.7 times higher compared with the control. The dirhamnolipid/monorhamnolipid ratio was 2.2 times higher. The additions of PQS at the time of inoculation are sufficient to induce RhlC activity during the transition to stationary phase.So, after 24 hours in the presence of 40, 60 or 80 μМ PQS rhamnosyltransferase 2 activity was higher at 40%, 70% and 120%, respectively, as compared with the control.